MEKANISME DAN SISTEM KEADILAN SOSIAL DISTRIBUSI DALAM EKONOMI ISLAM - Siti Hardianti Hemas (Fakultas Syariah Institut Agama Islam Negeri Palu, 2016)
Islam as a universal religion, very concerned for justice in human life. Especially to Muslims. Thus Islam has obliged the circulation of wealth occurs in members of the public, a ban on practices accumulated, hoarding on consumer goods, and goods production, because it would result in a very negative because it can damage all the systems that exist in the community and even the world as a whole, which resulted in an imbalance in covering various aspects of life which has been practiced by the capitalists and socialists. Therefore, Islam gives attention to the distribution system which took place in the community by providing strict rules that have been widely disclosed in the Qur'an and the hadith of the Prophet. In sharing the problems caused by economic inequality, it is necessary a social justice in the distribution system, namely economic equality.